2015
DOI: 10.1002/acn3.257
|View full text |Cite
|
Sign up to set email alerts
|

Network dysfunction in α‐synuclein transgenic mice and human Lewy body dementia

Abstract: ObjectiveDementia with Lewy bodies (DLB) is associated with the accumulation of wild‐type human α‐synuclein (SYN) in neurons and with prominent slowing of brain oscillations on electroencephalography (EEG). However, it remains uncertain whether the EEG abnormalities are actually caused by SYN.MethodsTo determine whether SYN can cause neural network abnormalities, we performed EEG recordings and analyzed the expression of neuronal activity‐dependent gene products in SYN transgenic mice. We also carried out comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
57
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(62 citation statements)
references
References 61 publications
5
57
0
Order By: Relevance
“…However, both increased seizure susceptibility and aberrant network excitability have been related to the overexpression of both tau protein and ␣-synuclein in animal models of FTD [40] and DLB [41]. Thus, the precise cause of epileptic seizures in patients with neurodegenerative dementias has not been fully elucidated yet, and it is likely underlined by complex mechanism and heterogeneous neuropathology.…”
Section: Discussionmentioning
confidence: 99%
“…However, both increased seizure susceptibility and aberrant network excitability have been related to the overexpression of both tau protein and ␣-synuclein in animal models of FTD [40] and DLB [41]. Thus, the precise cause of epileptic seizures in patients with neurodegenerative dementias has not been fully elucidated yet, and it is likely underlined by complex mechanism and heterogeneous neuropathology.…”
Section: Discussionmentioning
confidence: 99%
“…Overexpression of APP/Aβ and α-synuclein have each been associated with a reduction in calbindin in the hippocampi of transgenic animal models, and similar changes are observed in postmortem brain samples from patients with AD and DLB [18, 24]. …”
Section: Introductionmentioning
confidence: 94%
“…Additionally, apolipoprotein E4, the most common risk factor for AD, contributes to network hyperexcitability in animal models by causing tau-dependent decrease in GABAergic interneurons in the hippocampus [23]. Finally, overexpression of α-synuclein is sufficient to cause aberrant network excitability in experimental models of DLB, AD, and comorbidity [24]. …”
Section: Introductionmentioning
confidence: 99%
“…Cell culture and slice physiology studies demonstrated that pathological α-Syn perturbs normal synaptic function (Volpicelli-Daley et al, 2011;Wu et al, 2019), for instance, by oligomeric α-Syn's actions upon glutamatergic receptors (Durante et al, 2019). Further, brain-surface electroencephalography from transgenic mice overexpressing human α-synuclein, throughout the brain, uncovered aberrant activity, including epileptiform events (Morris et al, 2015). Our in vivo results suggest that elevations in pathological α-Syn, up to a particular level, may be sufficient to entail changes in synaptic coupling or perhaps efficacy which may result in the aberrant LFP activity.…”
Section: Beta Band Activitymentioning
confidence: 99%
“…Prior in situ and ex vivo studies have established that the natively unfolded form of α-Syn can modulate synaptic activity (Burré, 2015;Burré et al, 2010;Chandra et al, 2004). One study used brain surface electroencephalography to uncover changes in network activity of transgenic mice overexpressing human α-Syn (Morris et al, 2015).…”
Section: Introductionmentioning
confidence: 99%